Faktor yang Memengaruhi Pendapatan Margin Murabahah pada Bank Umum Syariah dan Unit Usaha Syariah - Adi Yulianto; Ade Ali Nurdin; Ine Mayasari (Journal of Applied Islamic Economics and Finance, 2021)
Murabahah contracts that become the most popular at Islamic banks are an important thing to study. Especially the determination of profit margins that do not have clear rules therefore things that can enlarge and reduce murabahah margin income are interesting to study. This study aims to determine the factors that can determine the murabahah margin income, as well as to find out the variables that predominantly influence the murabahah margin income. The objects used in this study are Sharia Commercial Banks and Sharia Business Units in Indonesia. The period used starts from 2014 untul 2018. The data used is secondary data then the data is processed using panel data regression method. The results show overhead costs, profit sharing of third party funds, volume of murabahah financing, and deposit rates have an influence on murabahah profit margins and inflation has no effect on murabahah profit margins. The volume of murabahah financing is a factor that has a dominant influence on murabahah profit margins.